Método da histerese por auto-ajuste para minimização de esforço de controle no separador submarino VASPS - De Melo, André V.; Serapião, Adriane B. S. [UNESP]; Mendes, José R. P. (My University, 2009)
This work presents a study of the development of a non-standard controller based on an auto-tuning hysteresis mechanism, in order to control the liquid level inside of a sub sea separation and pumping system. The developed controller generates signals, which are sent to the electrical submersible pump to control the liquid level in the separator's tank to avoid that it reach very low values, which could damage the pump, or very high values, which would reduce the liquid/gas separation efficiency. The controller must generate the minimum number of signals variations as possible to avoid wear on the pump and premature failures. In computer simulations, the developed controller was tested under large variations in operation conditions, such as slugs, with reliable and promising results.
Keywords: ESP; Hysteresis; Petroleum engineering; Smart control; Subsea separation